2017
DOI: 10.17140/antpoj-2-109
|View full text |Cite
|
Sign up to set email alerts
|

Second Digit Length, Fourth Digit Length and Second to Fourth Digit Ratio (2D:4D): Relevance in the Choice of Female Footballer Athletes and Female Non-Footballer Athletes in Nigeria

Abstract: Several studies have shown the importance of anthropometric measurements as a veritable tool in forensic science, crime detection, as well as a means of studying variations in human populations. The present study focused on using digit lengths and ratio to determine sports skills. A total of 270 female subjects comprising of sports and non-sports participants were measured. Seventy of which were non-footballer athletes, 100 were footballer athletes, and 100 were nonsports participants. The second and fourth di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The fourth digit is the ring finger of the human hand and the second most ulnar finger located between the middle finger and the little finger. The second digit is the index finger, which is the first finger and the second digit of the human hand (Oladipo et al 2017). Manning et al (1998) have suggested that the ratio between the lengths of the 2nd (index) and 4th (ring) fingers (the 2D:4D ratio), a sexually dimorphic trait with lower mean 2D:4D in males compared to females, is negatively related to prenatal testosterone and positively related to estrogen (Manning et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The fourth digit is the ring finger of the human hand and the second most ulnar finger located between the middle finger and the little finger. The second digit is the index finger, which is the first finger and the second digit of the human hand (Oladipo et al 2017). Manning et al (1998) have suggested that the ratio between the lengths of the 2nd (index) and 4th (ring) fingers (the 2D:4D ratio), a sexually dimorphic trait with lower mean 2D:4D in males compared to females, is negatively related to prenatal testosterone and positively related to estrogen (Manning et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the methodology of "2D: 4D" was also used by other specialists [46,[48][49][50][51][52]. Kamińska and Szymańska-Parkieta [53] studied a large group of schoolgirls of 13 years old and found that in physically more developed girls, the proportions of the fingers were close to male.…”
Section: Discussionmentioning
confidence: 99%